2010
DOI: 10.1289/ehp.1003089
|View full text |Cite
|
Sign up to set email alerts
|

San Antonio Statement on Brominated and Chlorinated Flame Retardants

Abstract: San Antonio Statement on Brominated and Chlorinated Flame Retardants (Signatories as of publication date. Institutions are for identification purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…In 2010 a group of over 100 eminent environmental scientists signed the San Antonio statement on halogenated flame retardants [81] condemning their continued use and requesting urgent remedial action. These persistent organic pollutants (POPs) take several years to break down in the environment, are bioaccumulative (they accumulate in plants and animals, becoming more concentrated as they move up the food chain), and are toxic.…”
Section: Fire Retardantsmentioning
confidence: 99%
“…In 2010 a group of over 100 eminent environmental scientists signed the San Antonio statement on halogenated flame retardants [81] condemning their continued use and requesting urgent remedial action. These persistent organic pollutants (POPs) take several years to break down in the environment, are bioaccumulative (they accumulate in plants and animals, becoming more concentrated as they move up the food chain), and are toxic.…”
Section: Fire Retardantsmentioning
confidence: 99%
“…In the past decades halogen based flame retardants, in particular the reactive tetrabromobisphenol A (TBBPA), have been used to suppress the flammability of EP [3]. However this leads to the production of corrosive, obscuring smoke and toxic halogenated compounds during the combustion of halogenated structures [4]. Therefore, some brominated compounds will be gradually phased out to comply with new environmental legislation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of detailed studies have demonstrated the toxicity of these releases to humans and animals [20]. In 2010, a group of over 200 concerned scientists signed the San Antonio statement on brominated and chlorinated flame retardants [21] questioning their continued use and requesting urgent remedial action. The flame retardants currently causing concern are small molecules which can easily migrate through the polymer matrix, with consequent release into the environment.…”
Section: Drivers For the Replacement Of Brominated Flame Retardantsmentioning
confidence: 99%